2014
DOI: 10.1108/mip-08-2013-0139
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' willingness to pay for ethical attributes

Abstract: The aggregated result shows that although consumers are willing to pay more for the product with ethical attributes than the one that is without, still around a half of them are not willing to pay more. In terms of demographics, the results show no significant differences between the two genders or different age groups in their willingness to pay for ethical attributes. As might be expected, willingness to pay was correlated with the level of consciousness of the ethical attributes.Originality/Value: The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
1
33
0
6
Order By: Relevance
“…Shaw and Clarke, 1999;Bray et al, 2011); reinforce how ethical factors and values, such as producers' welfare and concern for the environment, continue to influence heavily the purchasing decisions of Western households (see e.g. Tanner et al, 2003;Doran, 2010;Brenton, 2013;Mai, 2014); and provide an extended analysis of consumers' willingness to pay (e.g. Campbell et al, 2015) as well as how labelling influences their purchasing decisions (e.g.…”
Section: A Critical Overviewmentioning
confidence: 91%
“…Shaw and Clarke, 1999;Bray et al, 2011); reinforce how ethical factors and values, such as producers' welfare and concern for the environment, continue to influence heavily the purchasing decisions of Western households (see e.g. Tanner et al, 2003;Doran, 2010;Brenton, 2013;Mai, 2014); and provide an extended analysis of consumers' willingness to pay (e.g. Campbell et al, 2015) as well as how labelling influences their purchasing decisions (e.g.…”
Section: A Critical Overviewmentioning
confidence: 91%
“…Past consumer research on chocolate consumption and purchasing behaviour has focused strongly on the issue of sustainability and ethical consumption (nineteen out of fifty-four papers). Most of the reviewed literature on sustainable consumption and purchasing behaviour used a willingness-to-pay approach [3,4,17,21,30,34,36,42,44,45,47,55], five of which through the auction system [21,34,44,45,47]. The use of visual stimuli within the research studies that focused on sustainability issues has been applied in five studies [30,34,38,53,55].…”
Section: Methodological Approaches and Research Issues Of Selected Pamentioning
confidence: 99%
“…Among them, only one has projected a video [30], whereas the other research studies have employed images of existing products or images modified ad hoc for the experiment. The choice experiment methodological approach has been adopted in five studies [3,4,[16][17][18], using questionnaires and interviews as the data collection method. All papers dealing with sustainability issues have adopted questionnaires.…”
Section: Methodological Approaches and Research Issues Of Selected Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars Asian J. Market., 9 (1): 27-37, 2015(Bendixen et al, 2004Kumar et al, 2003;Mai, 2014;Trivedi et al, 2015) have found willingness to pay price premium as one of the key characteristics of customer commitment. A price premium according to theoretical economic literature can be described as excess price paid over and above the fair price that is justified by the true value of the product (Klein and Leffler, 1981;Rao and Bergen, 1992).…”
Section: Introductionmentioning
confidence: 99%